Comparison of electronic load using linear regulator and boost converter - Ayop, Razman; Md Ayob, Shahrin; Tan, Chee Wei; Sutikno, Tole; Abdul Aziz, Mohd Junaidi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Direct current (DC) electronic load is a useful equipment for testing the electrical system. It can emulate various load at a high rating. The electronic load requires a power converter to operate and a linear regulator is a common option. Nonetheless, it is hard to control due to the temperature variation. This paper proposed a DC electronic load using the boost converter. The proposed electronic load operates in the continuous current mode and control using the integral controller. The electronic load using the boost converter is compared with the electronic load using the linear regulator. The results show that the boost converter able to operate as an electronic load with an error lower than 0.5% and response time lower than 13 ms.